The effect of NaCl salinity on seed germination of Excoecaria agallocha L. - T. Balasubramanian1,2, P. Amuthavalli1,; P. Sivaraman1, S. Sivasankaramoorthy1, T. (Current Botany, 2011)
<span style="font-family: Byington; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The present work is based on the observation of seed germination in Excoecaria agallocha in different concentrations of NaCl. The seeds of Excoecaria agallocha were germinated in 0, 50, 100, 150 and 200 mM NaCl concentrations. The germinating seedlings were observed after 15th and 30th day of NaCl treatment. It was observed that the germination percentage were decreased with increasing NaCl salinity. The maximum percentage (100%) of seed germination was recorded in fresh water and the minimum percentage (36%) of germination was observed in 200 mM NaCl concentration.